Comparison of Dental and Bone Devices with Instantaneous Expansion of the Upper Jaw in Young People - Xayrullaevna, ORTIKOVA Nargiza (American Journal of Bioscience and Clinical Integrity, 2024)
Narrowing of the upper jaw is one of the most common anomalies, regardless of the type of dentition studied. They can be treated with either dental or bone dilators, depending on the biological maturation of the patient. Prepubescent treatment has been shown to be successful, but there is evidence of an open seam even in the late stages of adolescence.